Chicken Feather Powder as Corrosion Inhibitor for Aluminium in NaOH Solution - Manikandan, J.; Subramanian, R.; Chinnadurai, G.; Buvaneswari, S.; Manikam, N.; Mohamed Musthafa, A. (Asian Journal of Chemistry, 2015)
The effect of chicken feather powder (CFP) on the corrosion of aluminium (Al) in 0.5 M NaOH solution was examined using weight loss method. The inhibition efficiency of chicken feather powder on the corrosion of Al in 0.5 M NaOH solution increased with increasing concentration and immersion time whereas decreases with increasing temperature which shows that the adsorption occurred is physisorption. Inhibition action of chicken feather powder at different concentration and temperature were investigated. The adsorption of chicken feather powder on metal surface obeyed Langmuir adsorption isotherm. Weight loss method showed that the chicken feather powder acted as mixed inhibitor for Al in 0.5 M NaOH solution and follows physical adsorption on the surface of aluminium.